Non-Destructive Measurement of Green Bitter Gourd Quality Component Using Near Infrared Spectroscopy (NIRS) - Kusumiyati Kusumiyati; Wawan Sutari; Jajang Sauman Hamdani; Syariful Mubarok; Rika Bhernike Sitepu; Ade Risti Oktavia (Science and Technology Indonesia, 2018)
The quality component measurement of horticultural products becomes more important to achieve better quality products also to obtain uniform product. Recently, measurement by non-destructive methods turns out to be more needed, because consumers become more selective and demand producers to develop a quick, effective and accurate quality assessment system. Near Infrared Spectroscopy (NIRS) can measure plant contents quickly, relatively economical in a bigger scale, and importantly non-destructive. The measurement of quality components of green bitter gourd, such as firmness, water content, total soluble solid, and color, are important but have not been widely conducted. This research was conducted from June to August 2013 at Post Harvest Laboratory, Faculty of Agriculture, Padjadjaran University, Sumedang, Indonesia with PLS regression modeling method. The results show R-value and standard error of 0.91 and 0.47 for water content, 0.93 and 1.03 for firmness, and 0.95 and 0.49 for a* value of fruit color.